Revision of the genus Aleyda Schaus, 1928 with the description of one new species (Lepidoptera: Mimallonidae) - R. A. St Laurent; T. L. McCabe; T. Malm (SHILAP, 2018)
The genus Aleyda Schaus, 1928 is revised. The male of the type species of Aleyda, A. accipiter, is redescribed, and the female is figured for the first time. Aleyda heppneri St Laurent, McCabe & Malm, sp. n. from Panamá and French Guiana is newly described. Male and female genitalia of both species are figured for the first time.